Gambaran Kebutuhan Keluarga Pasien di Ruang Instalasi Gawat Darurat - I Putu Krisna Widya Nugraha; Dody Setyawan (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2019)
The patient's condition and the environment of the Emergency Installation (ER) that are unique can affect the psychological condition of the patient's family. This causes the emergence of psychological problems in the patient's family, such as anxiety, stress, and depression, these problems can affect the role of the family as a supporting system of patients in the process of handling actions while in the ER. These problems can be minimized by fulfilling family needs while in the ER to accompany the patient. The purpose of this study is to find out the description of the patient's family needs in the emergency room. This research is a descriptive quantitative study with a survey approach, with the research instrument in the form of a CCFNI-ED questionnaire. Respondents numbered 96 patient families obtained through convenience sampling techniques. The results of this study indicate that family needs which according to the family are important to fulfill are communication needs followed by understandable needs, support needs, comfort needs and needs close to the patient. Communication needs are considered the most important needs needed by the patient's family while in the emergency room. This research is expected to be a source of reference for the nursing profession in meeting family needs while in the emergency room, so it is expected to increase the family's role in healing patients.